Abortion Bans and Handmaid Protests: The Connectedness of The Handmaid’s Tale to the Disruption of Reproductive Rights - Tabuyo-Santaclara, Sara (International Journal of English Studies, 2024)
Margaret Atwood’s dystopian novel The Handmaid’s Tale has gained relevance in recent years due to the popularity of the series adaptation by showrunner Bruce Miller. The genesis of the novel is tightly bound to the sociopolitical context in which it was conceived in the 1980s while the show was released just a few months after Donald Trump’s election, both contexts marked by the looming threat of the limitation of access to safe abortion. The aim of this article is to analyze The Handmaid’s Tale as a cultural artifact that transcends the fictional realm and has spilled into the real world by inspiring a global protest movement against restrictions on reproductive rights. While the handmaid protest movement has garnered media attention, its articulation and effectiveness present limitations.